(3efgLjI GdHMK GdYdej ddLGeYjjf (B/s - (3TQhN, UdGM GdOjfs ((3GdLRGFQ (B: s (3OGQ GdYdhe ddfTQ hGdJhRjY(B, s)
(3jVe eaghe GdHMK GdYdej, JfajP GdHMK GdYdej, efGgL GdHMK GdYdej(B. s
(3HjHdjhZQGajG(B: (3U U(B.165-170s
Keywords: (3GdHMhKs; (3GdeSM GdYdejs; (3WQb GdHMKs